2020
DOI: 10.1108/medar-10-2019-0591
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory CSR expenditure and stock return

Abstract: Purpose India has mandated corporate social responsibility (CSR) expenditure under Section 135 of the Indian Companies Act, 2013 – the first national jurisdiction to do so. The purpose of this paper is to examine the impact of mandated CSR expenditure on firms’ stock returns by using actual CSR spending data, whereas the previous studies mostly focus on voluntary CSR proxied by CSR scores. Design/methodology/approach The authors estimate their baseline regression by using ordinary least squares(OLS) method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 60 publications
(107 reference statements)
1
31
2
Order By: Relevance
“…Current conditions indicate that CSR is not only related to social activities, but investors react more when companies care about the environment because the company primarily causes environmental damage/pollution that occurs. This study's results support research [17] [18] and [19], [20]. Our finding contradicts the findings [10] [11] [12] [13] [14] [15] which states that CSR improves company performance and [6] [16] explained that social responsibility has no impact on financial performance measured by ROA.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…Current conditions indicate that CSR is not only related to social activities, but investors react more when companies care about the environment because the company primarily causes environmental damage/pollution that occurs. This study's results support research [17] [18] and [19], [20]. Our finding contradicts the findings [10] [11] [12] [13] [14] [15] which states that CSR improves company performance and [6] [16] explained that social responsibility has no impact on financial performance measured by ROA.…”
Section: Resultscontrasting
confidence: 56%
“…Firm size and leverage this year improve future firm performance (ROAt + 1), large firm size has more significant resources for CSR expenditure and, therefore, engages in CSR-related activities to improve company performance in the future [23]. Companies with high debt tend to spend CSR expenditure on reducing information asymmetry with lenders and using debt to increase profitability in the future to improve company performance in the future [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that firms decreased their CSR spending after the law was enacted because of CSR’s reduced signaling value under the mandatory norms. Manchiraju and Rajgopal (2017) and Bhattacharyya and Rahman (2020) have examined the law’s impact on a firm’s performance. They have documented that the CSR law negatively affects a firm’s performance because mandatory CSR adds costs to the firm.…”
Section: Introductionmentioning
confidence: 99%